The Effect of Kinesiology Tape During Isotonic Knee Flexion Extension Exercise on Time to Fatigue, Rate, and Quadricep Muscle Oxygenation - (:unkn) unknown (My University, 2018)
Some Kinesiology Tape manufacturers claim that Kinesiology Tape (KT) can enhance performance and increase blood flow. Therefore, this study recruited 14 healthy male subjects (college population, 182.9 ± 5.1 cm, 76.52 ± 10.2 kg). to complete an eight-day KT intervention experiment. On Day 1 and Day 2 the subjects did not wear KT. During Days 3 to 6 the subjects wore the KT on their dominant leg (treatment leg) only. Limb dominance was defined by asking the subjects which leg they use to kick a ball. During Days 7 and 8 the subjects did not wear KT. Furthermore, the KT was not worn on the non-dominant leg (control leg) during the study. During testing each subject performed a fatiguing isotonic flexion/extension exercise with a single leg on a Biodex, and switched to the other leg after the first leg exercise was complete. Fatigue was defined by when a subject could no longer perform the exercise. The time to fatigue (TTF), number of cycles, and rate (number of cycles over TTF) were recorded as performance measures. Muscle oxygenation data including sitting baseline, minimum rSO2 levels, and time to minimum rSO2 levels in the trial were assessed to determine the influences of KT on blood flow. The confidence level ii in this research was set at 95%. The time series was analyzed to check the root cause of any performance enhancement. The results suggest that KT did not enhance the performance since the TTF and rate increased most of the days in both the taped and control legs. Furthermore, the time series analyses support the finding that the TTF and rate performance was enhanced by a learning effect. The muscle oxygenation results suggest the Vastus Medialis (VM) minimum rSO2 were increased by the KT. Even though the Vastus Lateralis (VL) sitting baseline show a statistically significant increase (p=0.045), the Power analysis suggest that the results need more subjects to avoid type I error. In conclusion, the KT type and brand utilized in this research did not support the manufacturers claim regarding enhanced performance. However, the muscle oxygenation results did show a difference when KT was on the treatment leg.
Keywords: Fatiguing exercise; Isotonic exercise; Kinesiology Tape; Muscle oxygenation